2017
DOI: 10.1038/srep42843
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Chinese Medicine Xinmailong’s protection against heart failure in pressure-overloaded mice and cultured cardiomyocytes

Abstract: Patients with heart failure (HF) have high mortality and mobility. Xinmailong (XML) injection, a Chinese Medicine, is clinically effective in treating HF. However, the mechanism of XML’s effectiveness on HF was unclear, and thus, was the target of the present study. We created a mouse model of pressure-overload-induced HF with transverse aortic constriction (TAC) surgery and compared among 4 study groups: SHAM (n = 10), TAC (n = 12), MET (metoprolol, positive drug treatment, n = 7) and XML (XML treatment, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…This activation of ERK1/2 is consistent with reports showing that TAC triggers ERK1/2 phosphorylation. [36][37][38] The inhibitory effect of gentisic acid on ERK1/2 activation was almost the same as that noted following administration of bisoprolol or dilti- that employed in our animal experiments was very high (70 times greater), possibly explaining the stronger reduction in TAC-associated cardiac fibrosis noted using this drug. In contrast, the diltiazem dose used in our investigation was three times higher than that given to patients (90 mg twice daily).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This activation of ERK1/2 is consistent with reports showing that TAC triggers ERK1/2 phosphorylation. [36][37][38] The inhibitory effect of gentisic acid on ERK1/2 activation was almost the same as that noted following administration of bisoprolol or dilti- that employed in our animal experiments was very high (70 times greater), possibly explaining the stronger reduction in TAC-associated cardiac fibrosis noted using this drug. In contrast, the diltiazem dose used in our investigation was three times higher than that given to patients (90 mg twice daily).…”
Section: Discussionsupporting
confidence: 77%
“…However, p38 and JNK1/2 activation was not clearly observed in hearts following 5 weeks of TAC. This activation of ERK1/2 is consistent with reports showing that TAC triggers ERK1/2 phosphorylation . The inhibitory effect of gentisic acid on ERK1/2 activation was almost the same as that noted following administration of bisoprolol or diltiazem.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated that PAE has many medicinal values and has been explored as an alternative remedy for many diseases, such as heart disease, cancer, burn wounds, gastric ulcer, and so on [2, 3]. Other researches have also found that PAE could suppress liver fibrosis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, periplaneta americana extract (PAE) has been explored as an alternative remedy for many diseases, such as heart disease, cancer, burn wounds, gastric ulcer, and so on [1-3]. Interestingly, PAE also has the effect of anti-liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent drugs represented by traditional Chinese medicine (TCM) have drawn increasing attention in HF treatment (7)(8)(9)(10)(11)(12)(13). Potentially relevant TCM characteristics include its multiconstituent and multitarget features (12); in addition, TCM has fewer adverse effects in some cases than in controls or with Western medication in some studies (11).…”
mentioning
confidence: 99%